UPAYA PEMBERDAYAAN KELUARGA DALAM MENGATASI KECEMASAN DENGAN INTRADIALITIK EXERCISE DAN FOOT HAND MASSAGE UNTUK PENINGKATAN KUALITAS HIDUP PADA PASIEN GAGAL GINJAL YANG DILAKUKAN HEMODIALISIS DI RSUD. DR. SOEDOMO TRENGGALEK - Hariyanto, Awan; Christiani, Mimik; Subekti, Arik (Politeknik Kesehatan Kemenkes malang, 2023)
Renal failure is an end-stage renal disease that needs proper treatment. Hemodialysis is one of the final options for treating kidney failure, however, this action can cause saturation and anxiety which can affect vital sign stability and can also affect the success of hemodialysis. Family empowerment in an effort to overcome anxiety can be done with Intradialytic Exercise and Foot Hand Massage as an effort to improve the quality of life of family members. This community service method includes health education, family involvement in intradialytic exercise and foot hand massage, measurement of family empowerment to overcome anxiety is observed based on blood pressure, pulse, respiration and anxiety levels. Family empowerment with the implementation of health education is very effective in increasing the knowledge of 30 participants after health education 24 family members knowledge increased well, family involvement in intradialityc exercise and foot hand massage from 30 family members response to anxiety systole blood pressure from 25 family members blood pressure more than 140mmHg decreased to 12 people, 29 family members stable respiration 16-20x/min, stable pulse 60-80x/min there were 16 family members, and there was a decrease in anxiety levels. Family empowerment in Intradialytic exercise and foot hand massage has a positive impact on vital signs, reduces anxiety and can improve the quality of life of hemodialysis patients